Greenland freshwater pathways in the sub‐Arctic Seas from model experiments with passive tracers. Issue 1 (25th January 2016) - Dukhovskoy, Dmitry S.; Myers, Paul G.; Platov, Gennady; Timmermans, Mary‐Louise; Curry, Beth; Proshutinsky, Andrey; Bamber, Jonathan L.; Chassignet, Eric; Hu, Xianmin; Lee, Craig M.; Somavilla, Raquel
Abstract: Accelerating since the early 1990s, the Greenland Ice Sheet mass loss exerts a significant impact on thermohaline processes in the sub‐Arctic seas. Surplus freshwater discharge from Greenland since the 1990s, comparable in volume to the amount of freshwater present during the Great Salinity Anomaly events, could spread and accumulate in the sub‐Arctic seas, influencing convective processes there. However, hydrographic observations in the Labrador Sea and the Nordic Seas, where the Greenland freshening signal might be expected to propagate, do not show a persistent freshening in the upper ocean during last two decades. This raises the question of where the surplus Greenland freshwater has propagated. In order to investigate the fate, pathways, and propagation rate of Greenland meltwater in the sub‐Arctic seas, several numerical experiments using a passive tracer to track the spreading of Greenland freshwater have been conducted as a part of the Forum for Arctic Ocean Modeling and Observational Synthesis effort. The models show that Greenland freshwater propagates and accumulates in the sub‐Arctic seas, although the models disagree on the amount of tracer propagation into the convective regions. Results highlight the differences in simulated physical mechanisms at play in different models and underscore the continued importance of intercomparison studies. It is estimated that surplus Greenland freshwater flux should have caused a salinity decrease by 0.06–0.08 in the sub‐Arctic seas in contradiction with the recently observed salinification (by 0.15–0.2) in the region. It is surmised that the increasing salinity of Atlantic Water has obscured the freshening signal. Key Points: Results from passive tracer model experiments are presented Greenland freshwater pathways and accumulation in the sub‐Arctic seas are analyzed Meltwater influence on salinity change in the sub‐Arctic is discussed